Decreased digit ratio (2D:4D) and gastric cancer in Chinese men. (December 2016) - Sheng, Youjing; Qian, Wenli; Wang, Lu; Huo, Zhenghao; Lu, Hong; Yu, Haochen; Geng, Zhi; Cheng, Ping
Abstract: Background: The development of finger length is influenced by the level of hormones during pregnancy in the womb. The relative length of 2nd to 4th digit (2D:4D) is considered as a putative marker for prenatal hormone exposure and may represent an individual susceptibility to certain diseases, particularly those hormone-related cancers (e.g., gastric cancer). Aims: The aim of this study is to investigate whether there is a possible relationship between 2D:4D ratio and gastric cancer (GCA) in Chinese men. Methods: 94 male patients with GCA and 91 controls were chosen to participate in this study. Photographs of both hands were collected and then the lengths of second and fourth digits of both hands were measured. Left hand, right hand, mean hand, and right minus left hand (∆ R-L) 2D:4D ratios were analyzed and compared. Results: In GCA group, 2D:4D ratios were significantly lower (right hand: p < 0.01; left hand, mean hand: p < 0.001) than controls. No association was observed between 2D:4D ratio and tumor staging (neither in tumor size (T) nor in lymph node involvement (N) or distant metastases (M)). There was also no correlation between 2D:4D ratio and age of onset. Conclusions: Decreased 2D:4D ratio may be an indicator for forecasting the susceptibility to develop GCA. Highlights: We investigated the relationship between digit ratio (2D:4D) and gastric cancer (GCA) in Chinese men. GCA patients had significantly lower 2D:4D ratio than controls. There was also no significant relationship between 2D:4D ratio and age of onset, tumor staging in GCA patients. Decreased 2D:4D ratio may be an indicator for forecasting the susceptibility to develop GCA.